Apocryphal Traditions in Kasper Miaskowski’s Christmas Poetry - Głuszak, Patrycja (Colloquia Litteraria, 2019)
The author, looking at the case of Christmas poems of Kasper Miaskowski, demonstrates the permanence and vitality of extra- -canonical Christmas components in Polish literature of the early seventeenth century. She presents individual elements of narratio Nativitatis extant in the writings of the poet from Smogorzewo, searching for an answer to the question about the means of transmission of the described components.